Calcium-fortified beverage supplementation effects on bone mineral density and body composition in healthy young women - Peterson, Kimberly Sue (Kansas State University, 2008)
BACKGROUND: Dietary supplements are increasing in popularity; individuals are looking beyond traditional methods of calorie restriction and exercise to improve health. Calcium is a critical nutrient for bone metabolism that has also been shown to enhance weight loss effects secondary to diet. PURPOSE: To determine whether eight months of calcium supplementation, in a liquid, shelf-stable form, increases bone mineral density or decreases body weight and/or body fat in free-living young adult women. METHODS: Volunteer subjects (n=42) were randomly assigned to a supplement group receiving 1,125 mg Ca2+/day (CA-BEV) or to a free-living control group (CON), which did not receive the supplement. At baseline and after the 8-month intervention (POST), dietary intake was assessed using 3-day diet records. Total body composition (body fat percentage, %FatTB; abdominal percentage fat, %FatAb; fat mass, FM; non-bone fat-free mass, FFM) and bone mineral density (lumbar spine and femoral neck; BMD) were measured via dual energy x-ray absorptiometry. Subjects also completed a sub-maximal treadmill exercise test to estimate respiratory fitness at baseline and POST. RESULTS: At POST, the CA-BEV group's calcium intake (1,868[plus or minus]941 mg/d) was significantly greater than (p<0.05) the CON group (867[plus or minus]405 mg/d) and the calcium:protein ratio of the CA-BEV group (29.5[plus or minus]17.1 mg/g) was greater than (p<0.05) the CON group (12.9 ±6.2 mg/g). Those differences in calcium did not lead to predicted differences (p<0.05) between groups for BMD, body weight, %FatTB, %FatAB, FM or FFM. CONCLUSION: Our findings do not support the hypothesis that increasing calcium intake increases BMD or decreases body weight or body fat in healthy young women over an 8-month period despite a nearly two-fold increase in calcium intake.
Keywords: obesity; overweight; osteoporosis; fat; Health Sciences, Nutrition (0570)